Nuclear peripheral chromatin-lamin B1 interaction is required for global integrity of chromatin architecture and dynamics in human cells - Chang, Lei; Li, Mengfan; Shao, Shipeng; Li, Chen; Ai, Shanshan; Xue, Boxin; Hou, Yingping; Zhang, Yiwen; Li, Ruifeng; Fan, Xiaoying; He, Aibin; Li, Cheng; et al. (Protein & cell, 2022)
The eukaryotic genome is folded into higher-order conformation accompanied with constrained dynamics for coordinated genome functions. However, the molecular machinery underlying these hierarchically organized three-dimensional (3D) chromatin architecture and dynamics remains poorly understood. Here by combining imaging and sequencing, we studied the role of lamin B1 in chromatin architecture and dynamics. We found that lamin B1 depletion leads to detachment of lamina-associated domains (LADs) from the nuclear periphery accompanied with global chromatin redistribution and decompaction. Consequently, the interchromosomal as well as inter-compartment interactions are increased, but the structure of topologically associating domains (TADs) is not affected. Using live-cell genomic loci tracking, we further proved that depletion of lamin B1 leads to increased chromatin dynamics, owing to chromatin decompaction and redistribution toward nucleoplasm. Taken together, our data suggest that lamin B1 and chromatin interactions at the nuclear periphery promote LAD maintenance, chromatin compaction, genomic compartmentalization into chromosome territories and A/B compartments and confine chromatin dynamics, supporting their crucial roles in chromatin higher-order structure and chromatin dynamics.